Modelamiento matemático de una celda de combustible de óxido sólido (SOFC), usando como combustible el gas de síntesis obtenido de la biomasa (2018)
We analize, by a mathematical modeling, the generation of electrical energy in a fuel cell, fed with synthesis gas from the process of gasification of residual biomass. One of the most interesting applications of synthesis gas is the generation of electric power, in an internal combustion engine; however, given the operating conditions of an engine and the content of pollutants (tars) in the synthesis gas, gas cooling processes and separation of these pollutants are required, which increase operating costs and reduce the overall efficiency of converting biomass into electricity. Due to the above, devices such as SOFCs have been studied since they can operate at the temperature of the gas at the gasifier outlet.